2016
DOI: 10.1111/jfpe.12439
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐Assisted Extraction of Apricot Kernel Oil: Effects on Functional and Rheological Properties

Abstract: An ultrasound-assisted procedure was applied to the extraction of oil from apricot kernels. The best possible combination of extraction parameters was obtained with the response surface methodology at a three-variable, three level experiments Box-Behnken design. The optimum extraction parameters were as follows: extraction time: 43.95 min; extraction temperature: 51.72 8C; and solvent/sample ratio: 19.8:01 at a fixed ultrasonic frequency of 40 kHz. Close agreement between experimental and predicted values were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…Regarding temperature, it can be seen that increasing the value of this variable increases the amount of oil extracted ( p < .05), as can be seen in Figure at times of 1,200, 3,600, and 7,200 s, for example. This increase is attributed to the thermodynamic effect of the temperature on the solubilization of the oil inside the sample, resulting from the reduction of the viscosity and the surface tension of the solvent and improvement of the diffusion coefficient (Chanioti & Tzia, ; Gayas, Kaur, & Gul, ; Sayyar, Abidin, Yunus, & Muhammad, ). Another parameter affected with temperature is the dielectric constant of the solvent, which directly intervenes in its polarity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding temperature, it can be seen that increasing the value of this variable increases the amount of oil extracted ( p < .05), as can be seen in Figure at times of 1,200, 3,600, and 7,200 s, for example. This increase is attributed to the thermodynamic effect of the temperature on the solubilization of the oil inside the sample, resulting from the reduction of the viscosity and the surface tension of the solvent and improvement of the diffusion coefficient (Chanioti & Tzia, ; Gayas, Kaur, & Gul, ; Sayyar, Abidin, Yunus, & Muhammad, ). Another parameter affected with temperature is the dielectric constant of the solvent, which directly intervenes in its polarity.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the increase in temperature favor the mass transfer of the extraction, increasing the diffusion of the oleaginous material to the ethanol and reducing the viscosity of the solvent (Chanioti & Tzia, ; Gayas et al, ), the addition of the temperature of 30–75°C favored the increase of the diffusion coefficient of 9.27 × 10 −12 –1.28 × 10 −11 m 2 s −1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…According to Gayas, Kaur, and Gul (2017) the extraction carried out at elevated temperatures causes softening of the plant tissues, promoting the removal of oil bound inside the matrix by the solvent used in the extraction process. This softening may be mainly related to an increase in the oil diffusion coefficient (Ramandi, Ghassempour, Najafi, & Ghasemi, 2017), which improves the oil diffusivity and solubility in the extraction solvent (Ramandi et al., 2017; Shirsath et al., 2017; Zhang et al., 2009), leading to a greater mass transfer (Massa et al., 2019; Ramandi et al., 2017; Zhang et al., 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Gayas et al (2017) observed the increase in oil yield of the apricot almond from 42% to 46% when the temperature was raised from 45 to 60°C in the ultrasonic bath Massa et al (2019). investigated the UAE of oil from seed/peel pumpkin at a temperature range of 30 to 75°C, using ethanol as a solvent.…”
mentioning
confidence: 99%
“…Process Intensification influences scientific and industrial activities, seeking innovation and implementation of practices and combining technologies in order to increase energy efficiency (Fernandez Rivas & Kuhn, ). In the food processing, ultrasound is applied to: antimicrobial effect, sterilization, milk pasteurization, protein modification, meat tenderizing and drying, liquid penetration into meat, homogenization and emulsification (milks and mayonnaises), nano emulsions containing essential oils, fermentation and aging of wine, crystallization, cutting of fresh and frozen products, anti‐foam action in carbonated beverages and aroma extraction, among others (Chemat, Zill‐E‐Huma, & Khan, ; Filippi, Bilibio, Bender, Carniel, & Priamo, ; Gayas, Kaur, & Gul, ; Leonelli & Mason, ; Mello, dos Santos Garcia, & da Silva, ; Rahman & Perera, ; Ricce et al, ; Salvia‐Trujillo, Rojas‐Graü, Soliva‐Fortuny, & Martín‐Belloso, ). The ultrasound technology has presented greater advantages when compared to other techniques: it is safer, nontoxic, and environmentally friendly.…”
Section: Introductionmentioning
confidence: 99%